Emerging Nano-Based Strategies Against Drug Resistance in Tumor Chemotherapy - Cao, Lei; Zhu, Yuqin; Wang, Weiju; Wang, Gaoxiong; Zhang, Shuaishuai; Cheng, Hongwei (Frontiers in Bioengineering and Biotechnology, 2021)
Drug resistance is the most significant causes of cancer chemotherapy failure. Various mechanisms of drug resistance include tumor heterogeneity, tumor microenvironment, changes at cellular levels, genetic factors, and other mechanisms. In recent years, more attention has been paid to tumor resistance mechanisms and countermeasures. Nanomedicine is an emerging treatment platform, focusing on alternative drug delivery and improved therapeutic effectiveness while reducing side effects on normal tissues. Here, we reviewed the principal forms of drug resistance and the new possibilities that nanomaterials offer for overcoming these therapeutic barriers. Novel nanomaterials based on tumor types are an excellent modality to equalize drug resistance that enables gain more rational and flexible drug selectivity for individual patient treatment. With the emergence of advanced designs and alternative drug delivery strategies with different nanomaterials, overcome of multidrug resistance shows promising and opens new horizons for cancer therapy. This review discussed different mechanisms of drug resistance and recent advances in nanotechnology-based therapeutic strategies to improve the sensitivity and effectiveness of chemotherapeutic drugs, aiming to show the advantages of nanomaterials in overcome of drug resistance for tumor chemotherapy.